2019
DOI: 10.1038/s41430-019-0463-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in diet quality and socioeconomic patterning of diet quality across ethnic groups: cross-sectional data from the HELIUS Dietary Patterns study

Abstract: Background/objectives Socioeconomic inequalities in diet quality are consistently reported, but few studies have investigated whether and how such inequalities vary across ethnic groups. This study aimed to examine differences in diet quality and socioeconomic patterning of diet quality across ethnic groups. Subjects/methods Cross-sectional data from the HELIUS study were used. Dutch, South-Asian Surinamese, African Surinamese, Ghanaian, Turkish and Moroccan adults (aged 18-70 years) were randomly sampled, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…Similar reasoning may apply to households with a self-employed household member compared to a day wage laborer or someone without a wage income. These results concur with those from studies showing that the employment status and educational level of the adult household members are associated with a greater demand for diversified diets [65,66].…”
Section: Discussionsupporting
confidence: 90%
“…Similar reasoning may apply to households with a self-employed household member compared to a day wage laborer or someone without a wage income. These results concur with those from studies showing that the employment status and educational level of the adult household members are associated with a greater demand for diversified diets [65,66].…”
Section: Discussionsupporting
confidence: 90%
“…Here, it was found that the probability of having a poor or moderate diet quality was greater in adults with CMD with a lower educational level compared with those without CMD with higher education. This is not the first time that a higher educational level has been associated with good dietary habits [97][98][99], although some studies have failed to find any association [100] or even found an inverse link [101,102], probably due to people with a higher educational level having access to better knowledge about food [103,104]. In addition, some studies have shown that a favorable attitude towards a healthy diet was associated with a higher educational level [105][106][107].…”
Section: Main Findingsmentioning
confidence: 94%
“…Previous studies show that children in rural and ethnic minority areas in central and western China have lower dietary diversity scores than those of their peers in other areas [ 62 , 63 ]. Investigators from the United States and Europe have also found that ethnic minority groups have poorer diet quality than those of ethnic majority groups [ 64 , 65 , 66 ]. Recent studies reveal ethnicity as an independent factor for diet quality [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%